Knowledge, Awareness and Preventive Practices of Dengue in Pakistan - Waris, Atija; Sajjad, Muhammad Mufeez; Ehsan, Talal; Hafeez, Sana; Sultan, Umar; Shalaby, Naglaa M (Indus Journal of Bioscience Research, 2025)
Objective: Dengue, a mosquito-borne disease has become endemic. This study was conducted to explore the knowledge, awareness and preventive practices of dengue in the Lahore district. This study was quantitative and a cross-sectional survey was conducted in the study area. Material and methods: A total of 160 randomly chosen respondents from the 20 public secondary schools participated in the survey. Data were collected through a structured, validated and reliable questionnaire. Collected data were analyzed using the Statistical Package of Social Sciences (SPSS). Descriptive statistics were applied to the data to explore the distribution of responses regarding knowledge, awareness and prevention practices against dengue. Results: The majority (86.9%) of respondents had heard about dengue fever and for 90.6% of respondents, Aides was the carrier of dengue. Around 56% of respondents had belied that Aedes breed in unclean water and 96.2% had a mistaken belief that it bites often at noon. Fever was the leading symptom (80.6%) and the use of mosquito repellent coil (98.8%), net (95%) and lotion (88.1%) were key preventive measures. Almost 76% of respondents were informed to visit the nearest Basic Health Unit (BHU) for urgent treatment followed by 21.2% of respondents favoring consulting a Hakeem (quacks) for the treatment. Conclusion: The school was the leading information source (80.6%) and the role of modern gadgets in awareness creating was dismal. This is suggested that community awareness level is obligatory, integration of modern gadgets in awareness campaigns is requisite, thus for high preventive measures synergistic strategy is needed.